Do hippos brush their teeth? : how animals care for their bodies - Kaner, Etta ([Do animals?], 2024)
"A delightful addition to the Do Animals... series, which includes Do Frogs Drink Hot Chocolate?, Do Lizards Eat Ice Cream?, and Do Fire Ants Fight Fires?, that playfully introduces young readers to more ways animal behavior is -- and isn't -- like ours. Just like humans, animals have unique routines to take care of themselves--from hygiene habits, to getting their vitamins, to treating wounds! Do hippos brush their teeth? NO!--not exactly. But they do have helpful fish friends that snack on the left over food bits and parasites stuck in hippos' mouths, leaving them squeaky clean as if they did own their own tooth brush. Do pheasants take baths? YES! They take "dust baths" which helps to get rid of sticky oil and parasites in their feathers. And do chimpanzees use hand wipes? SORT OF! Chimps use leaves to wipe away mud, sticky fruit juices, blood, and even poop! DO HIPPOS BRUSH THEIR TEETH? presents silly scenarios for 13 different animals practicing self-care--from axolotls using first aid kits to mend skateboarding wounds, to a giraffe using tissues to blow their nose--that will have kids laughing and learning. On the facing page of each spread, a more accurate rendering of the animal is accompanied by clear and concise text that explains the amazing ways animals work to survive - ways that are sometimes quite familiar! Etta Kaner's lively and inviting text is illustrated by delightfully funny and expressive digital art by Jenna Piechota."--Back cover